Pengembangan Bisnis: Strategi dan Solusi IT - Iga Dwi Wardanah; Khairunnisa Saragih; Muhammad Fauzan Azmi; Wiwin Khairany Simanjuntak; Nurbaiti Nurbaiti (Universitas Muhammadiyah Enrekang, 2022)
This iresearch iuses iqualitative imethod iwith idescriptive iresearch itype. iIn ithe ipresentation, ithe iresearch ierprovides ian ioverview iof ithe ibusiness imodel, ithen ievaluates iusing ia iSWOT ianalysis ion ieach ielement, iand icreates ia inew ione iat iPT iGojek. iRespondents ifrom ithis istudy iwere istudents iwho iused iGojek's ionline itransportation iservices. iThis istudy iuses idescriptive idata ianalysistechniques. There isults ishow ithat ibasedon iinternal istrengths iand iweaknesses,external iopportunities iand ithreats,foursets iof istrategic ialternatives imay ibe itaken iby icompany imanagers iin ifacing iincreasingly icompetitive iconditions.